An Analysis of Politeness Strategies Reflected by the Main Character in SpongeBob Movie: Sponge on The Run - Soegiarto, Herryono; Alawiyah, Rosidah; Syamsurrijal, Syamsurrijal (Jurnal Ilmu Sosial dan Humaniora, 2023)
Politeness is defined as a way to show awareness of another person’s public self-image. This research is a pragmatic study on politeness strategies stated by the main characters in The SpongeBob Movie: sponge on the run. The objectives of this research are to identify the types of politeness strategies employed by the main characters in The SpongeBob Movie: sponge on the run. This research used qualitative descriptive approach. The data used in this study were in the form of utterances which contain politeness strategies. The data source was The SpongeBob Movie: sponge on the run script. The data were collected by note-taking technique then they were classified and analyzed. The results of the research are showing that there are four types of politeness strategies employed by the main characters in The SpongeBob Movie: sponge on the run when having conversation such as Bald-on record strategy, Positive politeness strategy, Negative politeness strategy, and Off record strategy. Negative politeness is applied in as many as 7 times (35 %) by the main characters. At is followed by positive politeness strategy is applied as many 6 (30%) times the same as Bald-on Record strategy which is also occurred 6 (30%) times. On the other hand, Off-Record strategy is the least strategy applied by the main characters, it occurs once out of 20 (5 %).